E-cigarette use and associated factors among smokers with severe mental illness. (September 2020) - Peckham, Emily; Mishu, Masuma; Fairhurst, Caroline; Robson, Deborah; Bradshaw, Tim; Arundel, Catherine; Bailey, Della; Heron, Paul; Ker, Suzy; Gilbody, Simon
Highlights: Ever use of an e-cigarette was associated with having made a recent quit attempt and education level. People with SMI are interested in using an e-cigarette to help them stop smoking. The effectiveness of e-cigarettes as a smoking cessation aid in people with SMI should be explored. Abstract: Introduction: Smoking is more prevalent among people with severe mental illness (SMI) than the general population. E-cigarettes could provide an effective means of helping people to quit smoking. The aim of this paper is to explore the use of e-cigarettes and factors related to their use in people smokers with SMI. Methods: This is a cross sectional study including adult smokers with a documented diagnosis of SMI (ICD-10) recruited to the SCIMITAR + trial (2015–2016) from primary and secondary care. At baseline, participants were asked for demographic information and about their use of e-cigarettes. Data was were analysed to explore factors associated with e-cigarette use. After testing bivariate associations, logistic regressions were conducted. Results: Among 526 participants, 58.7% were male, mean age 46 years (SD 12.1), the majority (70.3%) had tried an e-cigarette. Among those who had ever tried an e-cigarette, over half (54.6%) reported the reason was to quit smoking, while 13.9% reported that the reason was to reduce smoking. Having an educational qualification of GCSE or higher (odds ratio 2.17, 95% CI 1.22 to 3.86, p = 0.008) and having made a quit attempt in the past six months (OR 1.66, 95% CI 1.04 to 2.63, p = 0.032) was associated with ever having tried an e-cigarette. Conclusions: Ever use of an e-cigarette was associated with education levels and recent quit attempts. Future trials could explore the effectiveness of e-cigarettes as a cessation aid in this participant group.